User-friendly extraction and multistage tandem mass spectrometry based analysis of lipid-linked oligosaccharides in microalgae - Pierre-Louis Lucas; Rodolphe Dumontier; Corinne Loutelier-Bourhis; Alain Mareck; Carlos Afonso; Patrice Lerouge; Narimane Mati-Baouche; Muriel Bardor (Plant Methods, 2018)
Abstract Background Protein N-glycosylation is initiated within the endoplasmic reticulum through the synthesis of a lipid-linked oligosaccharides (LLO) precursor. This precursor is then transferred en bloc on neo-synthesized proteins through the action of the oligosaccharyltransferase giving birth to glycoproteins. The N-linked glycans bore by the glycoproteins are then processed into oligomannosides prior to the exit of the glycoproteins from the endoplasmic reticulum and its entrance into the Golgi apparatus. In this compartment, the N-linked glycans are further maturated in complex type N-glycans. This process has been well studied in a lot of eukaryotes including higher plants. In contrast, little information regarding the LLO precursor and synthesis of N-linked glycans is available in microalgae. Methods In this report, a user-friendly extraction method combining microsomal enrichment and solvent extractions followed by purification steps is described. This strategy is aiming to extract LLO precursor from microalgae. Then, the oligosaccharide moiety released from the extracted LLO were analyzed by multistage tandem mass spectrometry in two models of microalgae namely the green microalgae, Chlamydomonas reinhardtii and the diatom, Phaeodactylum tricornutum. Results The validity of the developed method was confirmed by the analysis of the oligosaccharide structures released from the LLO of two xylosyltransferase mutants of C. reinhardtii confirming that this green microalga synthesizes a linear Glc3Man5GlcNAc2 identical to the one of the wild-type cells. In contrast, the analysis of the oligosaccharide released from the LLO of the diatom P. tricornutum demonstrated for the first time a Glc2Man9GlcNAc2 structure. Conclusion The method described in this article allows the fast, non-radioactive and reliable multistage tandem mass spectrometry characterization of oligosaccharides released from LLO of microalgae including the ones belonging to the Phaeodactylaceae and Chlorophyceae classes, respectively. The method is fully adaptable for extracting and characterizing the LLO oligosaccharide moiety from microalgae belonging to other phyla.